Novel structural features of the immunocompetent ceramide phospho-inositol glycan core from Trichomonas vaginalis - Heiss, Christian (Carbohydr Res, 2015)
The ceramide phosphoinositol glycan core (CPI-GC) of the lipophosphoglycan of Trichomonas vaginalis is a major virulent factor of this common genitourinary parasite. While its carbohydrate composition has been reported before, its structure has remained largely unknown. We isolated the glycan portions of CPI-GC by nitrous acid deamination and hydrofluoric acid treatment and investigated their structures by methylation analysis and 1- and 2-D NMR. We found that the α-anomer of galactose is a major constituent of CPI-GC. The β-anomer was found exclusively at the non-reducing end of CPI-GC side chains. Furthermore the data showed that the rhamnan backbone is more complex than previously thought and that the inositol residue at the reducing end is linked to a 4-linked α-glucuronic acid (GlcA) residue. This appears to be the most striking and novel feature of this GPI-anchor type molecule.